2019
DOI: 10.3390/insects10100344
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiological Bases of the Impact of Neonicotinoid Pesticides on the Behaviour of Honeybees

Abstract: Acetylcholine is the main excitatory neurotransmitter in the honeybee brain and controls a wide range of behaviours that ensure the survival of the individuals and of the entire colony. Neonicotinoid pesticides target this neurotransmission pathway and can thereby affect the behaviours under its control, even at doses far below the toxicity limit. These sublethal effects of neonicotinoids on honeybee behaviours were suggested to be partly responsible for the decline in honeybee populations. However, the neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 72 publications
1
28
0
1
Order By: Relevance
“…Each MG comprises a PN pre-synaptic bouton surrounded by multiple KC post-synaptic profiles, GABAergic neuron terminals (Ganeshina and Menzel 2001 ; Groh and Rössler 2020 ; Grünewald 1999a ), as well as modulatory input from octopaminergic and dopaminergic neurons (Blenau et al 1999 ; Hammer 1993 ; Zwaka et al 2018 ). The organization of pre- and post-synaptic terminals confers to the MG a spheroidal modular structure, that has been used to label them and quantify how their number and density in different areas of the MB calyces varies, e.g., with age, environmental factors, or after olfactory conditioning (Cabirol and Haase 2019 ; Groh et al 2012 ; Hourcade et al 2010 ; Scholl et al 2014 ).…”
Section: Honeybee Olfactory Systemmentioning
confidence: 99%
“…Each MG comprises a PN pre-synaptic bouton surrounded by multiple KC post-synaptic profiles, GABAergic neuron terminals (Ganeshina and Menzel 2001 ; Groh and Rössler 2020 ; Grünewald 1999a ), as well as modulatory input from octopaminergic and dopaminergic neurons (Blenau et al 1999 ; Hammer 1993 ; Zwaka et al 2018 ). The organization of pre- and post-synaptic terminals confers to the MG a spheroidal modular structure, that has been used to label them and quantify how their number and density in different areas of the MB calyces varies, e.g., with age, environmental factors, or after olfactory conditioning (Cabirol and Haase 2019 ; Groh et al 2012 ; Hourcade et al 2010 ; Scholl et al 2014 ).…”
Section: Honeybee Olfactory Systemmentioning
confidence: 99%
“…Since many ion channel genes and other important neuronal genes undergo extensive alternative splicing, they are prime targets for changes induced by xenobiotics 17,19 . Moreover, sub-lethal uptake of some neonicotinoids affects the honey bee brain, impairing foraging behaviour, flight, navigation, communication, learning and memory [20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…ng per bee per day for a 10 day chronic long-term exposure. A number of studies have used thiamethoxam doses in the same range for analysing changes in gene expression or observing an impact on behaviour following short term exposure18,[20][21][22][23][24]67,68 . In fact, it was found that chronic low-dose longterm thiamethoxam exposure altered bee activity, motor function and movement to light24 , but to our knowledge no previous analysis of gene expression under such conditions has been done.A key finding of our analysis of honey bee transcriptomes is the highly enriched fraction of dose-responsive, uncharacterised genes encoding short open reading frames (sORFs).…”
mentioning
confidence: 99%
“…A major anthropogenic factor influencing the insect olfactory system are insecticides remaining in the environment for a long time. Especially sublethal doses of neonicotinoid insecticides were shown to have negative effects on pollinating insects, such as honeybees and bumblebees, including decreased behavioral responses to attractive olfactory cues and impaired short-term memory, probably due to increased expression of nicotinic acetylcholine receptor expression and increased neural sensitivity to acetylcholine (Desneux et al 2007 ; Wright et al 2015 ; Cabirol and Haase 2019 ). Opposite to decreased olfactory responses, sugar sensitivity in honeybees increased after treatments with sublethal doses of the neonicotinoid acetamiprid (El Hassani et al 2008 ).…”
Section: Context-dependent Plasticity and Modulationmentioning
confidence: 99%